The association between oxidative stress and corneal hysteresis in patients with glaucoma - Uchida, Keiko (Sci Rep, 2020)
Systemic antioxidative status has been implicated in glaucoma pathogenesis. Additionally, corneal hysteresis (CH) may contribute to glaucoma progression. Here, we evaluated the relationship between biological antioxidant potential (BAP) and CH. This study included 103 patients with open-angle glaucoma (OAG). We used a free radical analyzer to measure BAP, and an ocular response analyzer to measure CH and corneal resistance factor (CRF). We evaluated the relationship between systemic oxidative stress and other clinical parameters with Spearman’s rank correlation test and a multi-regression analysis. BAP was not correlated to either CH or CRF in the male or female OAG patients. BAP was correlated to both CH and CRF in the female OAG patients older than 57 years (r = 0.51, P = 0.003; r = 0.49, P = 0.004), but uncorrelated in the female OAG patients younger than 57 years. Multiple regression analysis revealed that BAP independently contributed to CH (P = 0.025) and CRF (P = 0.015) in the older female OAG patients. Systemic oxidative stress may significantly affect the viscoelasticity of the cornea in older female OAG patients. Future studies are needed to confirm that low systemic antioxidative status and low corneal hysteresis contribute to glaucoma pathogenesis.